Population-based cervical cancer screening using highrisk HPV DNA test and liquid-based cytology in Northern Thailand - Sumalee Siriaunkgul (2018)
Background: Northern Thailand is a region with a high cervical cancer incidence. Combined high-risk HPV (hrHPV) DNA testing and cytology (co-testing) has increasingly gained acceptance for cervical cancer screening. However, to our knowledge, data from a population-based screening using co-testing have not been available in this region. This study therefore aimed to evaluate the performance of cytology and hrHPV test in women in northern Thailand. Materials and Methods: Cervical samples were collected for hybrid capture 2 (HC2) testing and liquid-based cytology from women aged 30 to 60 years who were residents in 3 prefectures of Chiang Mai in northern Thailand between May and September 2011. Women with positive cytology were referred to colposcopy, while women with positive for HC2 only were followed for 2 years. Results: Of 2,752 women included in this study, 3.0% were positive in both tests, 4.1% for HC2 only, and 1.3% had positive cytology only. At baseline screening, positive HC2 was observed in 70.6% among cytology-positive women compared with 4.3% among cytology-negative women. The prevalence of positive HC2 or cytology peaked in the age group 35-39 years and was lowest in the age group 55-60 years. High-grade squamous intraepithelial lesion or worse lesions (HSIL+) were histologically detected in 23.5% of women with positive baseline cytology and in 9.8% of women with positive baseline HC2 only on follow-up. All women with histologic HSIL+ had positive baseline HC2. Conclusions: The hrHPV test is superior to cytology in the early detection of high-grade cervical epithelial lesions. In this study, the prevalence of histologic HSIL+ on follow-up of women with positive hrHPV test was rather high, and these women should be kept under careful surveillance. In northern Thailand, hrHPV testing has a potential to be used as a primary screening test for cervical cancer with cytology applied as a triage test.